KEDUDUKAN ANAK PASCA-PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Robert Libra; Jumni Nelli (Jotika English and Education Center, 2024)
The Constitutional Court has made a revolutionary decision in MK decision Number 46/PUU-VIII/2010 concerning the status of children outside of marriage which states that, children born outside of marriage not only have a civil relationship with their mother and their mother's family, but also have a civil relationship. with his biological father which can be proven based on science and technology. This decision became controversial among the public, especially Islamic legal figures, because the Constitutional Court Decision No. 46/PUU-VIII/2010 concerning the status of illegitimate children resulted in major changes regarding the position of children in marriage law. This Constitutional Court's decision is the basis for the Banten High Court's consideration, that based on the Constitutional Court's decision 46/PUU/2010 as explained by the Plaintiff/Appellant's expert witness Arist Merdeka Sirait that children born out of wedlock have a civil relationship with their mother and their mother's family as well as with their father. those who can be proven based on science and technology or other evidence which according to law have a basic relationship including a civil relationship with their mother; Case Number 109/PDT/2022/PT BTN between Rezky Adhitya Dradjamoko and Wenny Ariani Kusumawardani in deciding the status of Rezky Adhitya's child, Naera Kamita.